Surgical –Audit on breast cancer risk factors in AL-Russafa district in Baghdad - . Ajoob, Rasim D; Hassani, Harith S.; Abudlhameed, Jamal R. (AL-Kindy College Medical Journal, 2015)
Background: Breast cancer remains a substantial cause of morbidity and mortality, there is a need for continued efforts to understand the etiology of the disease, maintain screening effort, implement prevention strategies, and develop better treatments.Objective: To analyze the risk factors, improve early detection and prevention of breast cancer in Al-Russafa district- Baghdad, aiming to increase survival rate and improve the quality of life.Methods: A cross sectional audit of 258 breast cancer cases seen at Al-Elwiya maternity teaching hospital from January2009 to December 2011,data collected from patients files were: age, gender , residency, marital status, parity, age at menarche and menopause age at first live birth, hormonal therapy, social habit, previous breast diseases, breast feeding and family history of breast cancer.Results: Two hundred fifty eight female diagnosed with breast cancer, age ranging from 20 to 79 years. Breast cancer was more prevalent in the fourth and fifth decade of life. The distribution was according to residency sectors, 10% were unmarried; fourteen percent nultiparous, the age at menarche was prevalent in 12 and 13 years old. Menopa-ausal age was at the fifth decade and age of patients at first live child at twenties. Forty two % received contraceptive hormonal therapy, 15% had previous breast diseases, 20% with family history of breast cancer, 24% non-breastfeeding and 6% smokers.Conclusion: Risk factors of breast cancer in Baghdad is a perplexing issue and needs a privy analysis as the disease has a para amount importance with increasing incidence in last decade. Knowing the risk factors for breast cancer may help us take preventive measures to reduce the likelihood of developing the disease and develop better treatment.Keywords: Breast cancer, Risk factors, surgical audit.Background: Breast cancer remains a substantial cause of morbidity and mortality, there is a need for continued efforts to understand the etiology of the disease, maintain screening effort, implement prevention strategies, and develop better treatments.Objective: To analyze the risk factors, improve early detection and prevention of breast cancer in Al-Russafa district- Baghdad, aiming to increase survival rate and improve the quality of life.Methods: A cross sectional audit of 258 breast cancer cases seen at Al-Elwiya maternity teaching hospital from January2009 to December 2011,data collected from patients files were: age, gender , residency, marital status, parity, age at menarche and menopause age at first live birth, hormonal therapy, social habit, previous breast diseases, breast feeding and family history of breast cancer.Results: Two hundred fifty eight female diagnosed with breast cancer, age ranging from 20 to 79 years. Breast cancer was more prevalent in the fourth and fifth decade of life. The distribution was according to residency sectors, 10% were unmarried; fourteen percent nultiparous, the age at menarche was prevalent in 12 and 13 years old. Menopa-ausal age was at the fifth decade and age of patients at first live child at twenties. Forty two % received contraceptive hormonal therapy, 15% had previous breast diseases, 20% with family history of breast cancer, 24% non-breastfeeding and 6% smokers.Conclusion: Risk factors of breast cancer in Baghdad is a perplexing issue and needs a privy analysis as the disease has a para amount importance with increasing incidence in last decade. Knowing the risk factors for breast cancer may help us take preventive measures to reduce the likelihood of developing the disease and develop better treatment.